TINGKAT PEMAHAMAN GURU TERHADAP PENILAIAN HASIL BELAJAR BERDASARKAN KURIKULUM 2013 PADA PROGRAM KEAHLIAN TEKNIK KONSTRUKSI DAN PROPERTI DI SMK N SE-KOTA PADANG - Dimas Aprian; Dr. Rijal Abdullah, MT (CIVED, 2019)
Abstract- The aims of assessement based 2013 curriculum  wasto determine the achievement of learner competencies. This curriculum emphasized authentic assessement,that  include the domain of the attitude assessement, knowledge and skill was expected to able to shape the student character. Teacher education qualification were expected to have mastered role in it. The obstacle faced by teacher in the assessment include the lack of training and many teacher who have not mastered the computer operation. Based on this background, a study was conducted which aimed to find out how well the teachers level of understanding of the learning outcomes assessement based on the 2013 curriculum on contruction and property engineering study programs at SMK N in the Padang City and in terms of educational qualifications. This research was descriptive type with a population of 41 teachers in the construction and property engineering program at SMK N 1 Sumbar, SMK N 1 Padang, and SMK N 5 Padang. Data collection is done using a questionnaire with a Likert scale that has 4 alternative answers and consist of positive and negative statements. Statement items totaling 49 pieces. The result of the study show that the level of teacher understanding in 2013 curriculum assessement is classified into fairly good category, namely: the concept of assessement is categorizied as good. In the implementation, development, and processing of assessements are quite good category. Keywords: Level of Understanding, Authentic Assessement, 2013 Curriculum.